SOSIAL MEDIA SEBAGAI SOLUSI STRATEGIS E-MARKETING DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN DI KEDAI KOPI BANJARAN - Wardani, Yudha; Wibowo, Andri; Rizki Muttaqien, Raden (Puslitabmas Batam Tourism Polytecnic, 2025)
This study investigates the role of product quality and social media-based e-marketing in shaping consumer purchasing decisions for coffee in Banjaran. Using a quantitative approach, data will be collected from customers of selected Banjaran coffee shops, analyzing how perceived product excellence and social media marketing (e.g., Instagram promotions, influencer collaborations, or online engagement) collectively drive buying behavior. Statistical methods, such as regression analysis, will determine the strength of these factors’ influence. The findings aim to provide actionable insights for Kopi Banjaran businesses to refine their product offerings and leverage social media strategies effectively, thereby enhancing customer attraction and sales performance.